The barriers to co-operation in the food safety system in Poland - Jendza, Dorota; Wróbel, Piotr (Journal of Public Governance, 2019)
Objectives: The official food safety system in Poland is divided between a number of specialised inspection bodies. The effective implementation of the entire inspection and supervision process requires multi-direction co-operation. The aim of the study presented was the identification of the barriers to and boundaries of the inter-organisational cooperation between the inspection bodies involved in the official food safety process. Research Design & Methods: Qualitative research methods: analysis of organisational documentation, industry reports, post-audit reports and in-depth interviews with employees of five inspection bodies. Findings: The co-operation between the inspection bodies should be multi-threaded and multi-lateral. In fact, the mechanisms that encourage co-operation are relatively weak and there are numerous barriers between them. The lack of the inter-organisational co-operation is caused by various factors: cultural, social, political, legal, and organisational norms and values. The key source of the barriers is the fragmentary perception of the food safety supervision process by employees, which results from the lack of a systematic approach to this process. The employees of the inspection bodies perceive the remaining inspections as external entities and not co-workers taking part in a common process aimed at common good. Implications/Recommendations: This article suggests some policy implications. The evolutionary solutions may include measures to eliminate the differences between inter-organisational co-operation postulated in legal regulations and real practices. The revolutionary activities may consist of building a comprehensive system of official food safety which will lead to consistent supervision over the entire food chain, and not only over the individual stages thereof. The construction of such a system may require changes in the number and the scope of tasks of the existing inspections. Contribution/Value Added: The inter-organisational co-operation problems as part of the official food safety process are not specific to only the system in Poland: similar difficulties are found in many countries. Therefore these research findings have potentially wide application.